Determination of Overpressure Zone and Its Mechanism in Baong Formation of the "Y" Field in North Sumatera Basin - Andrea Hasbullah; Hendra Amijaya; Jarot Setyowiyoto (Journal of Applied Geology, 2023)
The “Y” Field is one of the offshore areas in the North Sumatra Basin which is believed to have an important role in hydrocarbon exploration in the future. The North Sumatra Basin is known as an area that has high overpressure conditions and sometimes overpredicts in determining the amount of overpressure, especially in the Baong Formation. The purpose of this research is to determine the top and bottom overpressure zones, to know the vertical distribution of overpressure, and to find the main factors causing the overpressure in the Baong Formation.The data used in this study were 5 wells which have wireline log data, formation pressure data, leak of test, final well reports, mud logs, as well as 29 lines of 2D seismic data and 1 3D seismic data. The method used in this study was the Eaton method to determine pore pressure whereas the cross-plot wireline log method, the AI (acoustic impedance) inversion method and the stacking velocity were used to determine pore pressure.The study indicated that the overpressure zone is located in the Baong Formation at 1650 - 2108 m depth with a pore pressure of around 2891.70 - 3580 psi.  The overpressure is caused by loading mechanism, namely disequilibrium compaction. This is influenced by the thickness of the formation above Baong Formation.